ANALISIS WACANA KRITIS MODEL TEUN A. VAN DIJK PADA IKLAN MARJAN 2025 - kamilia, laila (STKIP PGRI SUMENEP, 2025)
This study aims to analyze the discourse in the Marjan Ramadan 2025 Episode 1 advertisement using the Critical Discourse Analysis approach of Teun A. van Dijk model, which includes three main structures: macro structure, superstructure, and micro structure. The 1-minute 10-second advertisement features a futuristic narrative with local cultural figures such as Mpu Baradah and Calon Arang that is packaged in a conflict between technology and spirituality. The results show that in macro structure, the main theme of the ad is the battle between the dominance of technology and the power of spiritual values, especially mother's love. In the superstructure, the advertisement is organized in a short narrative that is dense and symbolic, with binary opposition patterns such as creation vs creator and technology vs sincerity. In the microstructure, the use of symbolic language and dramatic visuals that reinforce the ideological message are found. In conclusion, this advertisement not only offers products, but also inserts cultural and ideological messages that traditional values such as prayer and love remain relevant in the digital era. This study recommends that people be more critical of the content of media messages, and opens up opportunities for further studies on cultural representations in advertisements.